2015
DOI: 10.1038/jhh.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hypertension prevalence, awareness, treatment and control among participants in the International Mobility in Aging Study (IMIAS)

Abstract: The aim of this study is to assess the factors associated with hypertension prevalence, awareness, treatment, and control, in the elderly populations of the International Mobility in Aging Study (IMIAS). Approximately 200 men and 200 women aged 65-74 years were recruited at each site (n=1995) during IMIAS' 2012 baseline survey at five cities: Kingston (Canada), Saint-Hyacinthe (Canada), Tirana (Albania), Manizales (Colombia) and Natal (Brazil). Blood pressure and anthropometric measurements were taken at parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
6
25
0
5
Order By: Relevance
“…Since these cities are located in one of the wealthiest regions in Brazil, a better knowledge of hypertension and the importance of the use of antihypertensive drugs emphasized in extensive public campaigns could explain these numbers. The higher prevalence of hypertension awareness and use of antihypertensive drugs in women have also been observed in other studies [ 24 , 27 , 28 , 30 ].…”
Section: Discussionsupporting
confidence: 78%
“…Since these cities are located in one of the wealthiest regions in Brazil, a better knowledge of hypertension and the importance of the use of antihypertensive drugs emphasized in extensive public campaigns could explain these numbers. The higher prevalence of hypertension awareness and use of antihypertensive drugs in women have also been observed in other studies [ 24 , 27 , 28 , 30 ].…”
Section: Discussionsupporting
confidence: 78%
“…We addressed this issue in previous publications reporting that according to census data, the Saint-Hyacinthe sample is comparable to the population of the same age group in the selected cities in terms of education, income and education and that the Kingston sample is relatively more highly educated. Kingston is, nevertheless, similar to the sample in Saint-Hyacinthe in terms of blood pressure, 57 C reactive protein, 58 physical function indicators 31 and distributions of SRH, depression and quality of life as reported here. It is nevertheless important to mention that the study samples are limited to older adults registered with a primary care provider, and that study samples in Canada are likely to be less depressed than the general population of older adults, given that they had to contact the research coordinator to participate in the study.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies reported that both urban and rural areas in Haikou showed a lower prevalence of chronic conditions than some of the northern provinces of China [ 12 – 15 ] and other developing countries [ 16 – 19 ]. According to previous finding, the lower prevalence of chronic diseases in Haikou could be ascribed to there being fewer smokers (18.3%), lower alcohol consumption (19.7%) and fewer overweight (17.5%) and obese (4.1%) people [ 20 ].…”
Section: Discussionmentioning
confidence: 99%